2010
DOI: 10.2174/157016210794088191
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators for Adherence to Antiretroviral Therapy in Papua New Guinea

Abstract: Papua New Guinea (PNG) is in a phase of scaling up access to antiretroviral therapy (ART), and adherence to the newly available drug therapy is becoming an important issue. This paper examines adherence to ART in a sample of 374 HIV-positive people in six provinces in PNG. Participants were recruited to the study using non-probability sampling. Sixty-two % of participants reported complete adherence (no missed or late doses in the past week) and 79% reported not missing any doses in the last week. Revival chur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…The prevalence of foreskin cutting in this study was higher than the 25.8% longitudinal cut and 3.4% circumferential cut documented in recent studies in plantation workers in the Highlands region, but similar to studies in the national capital [61-63,65]. The deliberate approach to include participants from diverse geographic locations and cultural backgrounds allowed a sample with a similar regional proportionality to the PNG population.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The prevalence of foreskin cutting in this study was higher than the 25.8% longitudinal cut and 3.4% circumferential cut documented in recent studies in plantation workers in the Highlands region, but similar to studies in the national capital [61-63,65]. The deliberate approach to include participants from diverse geographic locations and cultural backgrounds allowed a sample with a similar regional proportionality to the PNG population.…”
Section: Discussionsupporting
confidence: 67%
“…A National HIV/AIDS Behavioural Surveillance Study in 2006 documented 26 – 70% of men had some form of foreskin cut, however the study did not differentiate between the ‘round cut’ or ‘straight cut’ [61]. More recent studies have made the distinction [62,63] and found 25 - 50% of men had some form of foreskin cut, with considerable diversity in the extent and type of foreskin cut reported. Qualitative studies are expanding knowledge about beliefs and practices of the various styles of foreskin cutting, and their implications for HIV prevention in PNG [45,46,57].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the role of others, particularly health care workers, influencing a person’s beliefs and therefore decisions about sexual behaviour were also deemed important. This is not surprising since adherence to ART was also related to following instruction from the doctor/health care worker [46]. As people stay on treatment and as people live longer it will be important to chart if and how sexual behaviour changes and if the meanings ascribed to sexual intercourse and condom use similarly alter.…”
Section: Discussionmentioning
confidence: 99%
“…While the epidemic in PNG is primarily linked to heterosexual transmission [17,18] and the national population estimate is now below 1 per cent, considerably higher rates of HIV are found amongst more at risk populations such as people who sell sex. A 2010 bio-behavioural survey in Port Moresby [19] found that 17% of the sex worker population were HIV-positive. PNG is urgently trying to find alternative means of stemming the incidence of HIV.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted among attendees at an STI clinic in Lae, Morobe Province [28], a fifth of men reported having undergone full MC (20.3%) while over 40% reported having a dorsal slit and 16% reported a penile insert. Unpublished data from the most recent integrated bio-behavioural survey of sex workers in Port Moresby [19,40] found that of the males who sold sex 55.26% reported having undergone a penile cut of some form with proportionally fewer self identifying transgender than men reported being cut (46.4% vs 60.4% respectively). Of those that reported a cut slightly more than half (52.4%) reported a dorsal slit or other cut that was not round and did not result in full foreskin removal.…”
Section: Introductionmentioning
confidence: 99%